Chinese herbal injections combined with rt-PA intravenous thrombolysis for acute ischemic stroke: A systematic review and meta-analysis protocol - Wu, Jing (Medicine (Baltimore), 2021)
BACKGROUND: Acute ischemic stroke (AIS) is an important factor leading to adult death and disability globally. For AIS patients who meet certain conditions, recombinant tissue plasminogen activator (rt-PA) intravenous thrombolysis is an important method recommended by national guidelines to achieve vascular recanalization. However, complications such as hemorrhagic transformation and vascular reocclusion after thrombolysis are still unsolved problems in clinical. Several systematic reviews of clinical randomized controlled trials (RCTs) in the past have shown that Chinese herbal injections (CHIs) can improve the neurological function of patients, increase the tolerance of ischemic tissues to hypoxia, and inhibit platelet aggregation. Therefore, this study conducted a meta-analysis of AIS treatment with intravenous thrombolysis alone and compared it with the combined application of CHIs. To evaluate whether CHIs have a synergistic effect on thrombolytic therapy and provide a basis for clinical application. METHODS: The following databases will be searched until September 2020: ①English databases: PubMed, Cochrane Library, Embase; ②Chinese databases: CNKI, Wanfang database, Weipu database, SinoMed. RCTs will be included to compare the efficacy of thrombolysis combined with CHIs and thrombolysis alone in the treatment of AIS. Data extraction and risk of bias assessments will be carried out by 2 verifiers independently. The risk of bias will be evaluated through the Cochrane risk of bias tool. Review Manager software 5.3 will be used for statistical analysis. RESULTS: This study will provide comprehensive evidence for the treatment of AIS by CHIs combined with intravenous thrombolysis from multiple aspects. CONCLUSION: The conclusion of the meta-analysis will provide a basis for judging whether CHIs combined with intravenous thrombolysis is an effective measure for the treatment of AIS. ETHICS AND DISSEMINATION: Ethical approval is not needed because this study will be based on data that already published. We will publish the findings of this study in a peer-reviewed journal and related conferences. PROSPERO REGISTRATION NUMBER: CRD42020215546.